2004
DOI: 10.1590/s0100-879x2004000600007
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of hippocampal signal intensity in patients with familial mesial temporal lobe epilepsy

Abstract: Mesial temporal lobe epilepsy (MTLE) is associated with hippocampal atrophy and hippocampal signal abnormalities. In our series of familial MTLE (FMTLE), we found a high proportion of hippocampal abnormalities. To quantify signal abnormalities in patients with FMTLE we studied 152 individuals (46 of them asymptomatic) with FMTLE. We used NIH-Image ® for volumetry and signal quantification in coronal T1 inversion recovery and T2 for all cross-sections of the hippocampus. Values diverging by 2 or more SD from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…38 Nonetheless, structural abnormalities outside the mesial portion of the temporal lobe were similar in both forms of MTLE. 44 These findings, combined with previous results, 32,33 suggest that genetic factors may predispose some individuals to develop hippocampal abnormalities that may be further intensified by recurrent seizures; 30 however, to date, no studies addressing the molecular mechanisms possibly involved in familial MTLE have been performed, including gene expression analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…38 Nonetheless, structural abnormalities outside the mesial portion of the temporal lobe were similar in both forms of MTLE. 44 These findings, combined with previous results, 32,33 suggest that genetic factors may predispose some individuals to develop hippocampal abnormalities that may be further intensified by recurrent seizures; 30 however, to date, no studies addressing the molecular mechanisms possibly involved in familial MTLE have been performed, including gene expression analysis.…”
Section: Discussionmentioning
confidence: 93%
“…35,46 Family history of epilepsy was considered positive when the patient had at least two first-or second-degree relatives with MTLE, as defined by diagnostic criteria proposed previously and accepted by the literature in the field of epilepsy and by the International League Against epilepsy. 2,3,7,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]45 None of the patients included in the present study had any generalized or complex partial seizures documented 48 h before or during epilepsy surgery. This project was approved by the Research Ethics Committee of the University of Campinas (ethics approval # CAAE: 12112913.3.0000.5404), and all patients signed a consent form to donate part of the surgical tissue to research.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…In the present study we used MRI signs of HAb to classify individuals as affected, independently of the presence of seizures (individual I-2, F-10; Kobayashi et al, 2002, 2003; Coan et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…HA with or without hyperintense T2 signal on MRI was observed in most patients, including those with a single focal seizure, seizure remission (Kobayashi et al, 2003) as well as in 34% of asymptomatic first-degree relatives of patients with familial MTLE (Kobayashi et al, 2002). These reports suggest that hippocampal abnormalities (HAb) identified by MRI in familial MTLE have a genetic predisposition and it is not necessarily associated to seizures in all patients (Kobayashi et al, 2001; Coan et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Although the dentate gyrus, the CA1, CA4 and to a lesser degree CA3 sections of the hippocampus are primarily involved, regional involvement may be difficult to characterize on clinical MRI exams and does not impact the clinical management of the patients. On MRI, coronal T2-w and FLAIR images are the most sensitive for detecting abnormal signal, while T1 3D can better define the loss of hippocampal gyration (34). Some authors (35) have reported that MR qualitative imaging have a sensitivity ranging from 80% to 90% in the evaluation of mesiotemporal sclerosis while using quantitative assessment the sensitivity rises to 90% to 95%.…”
Section: Mesiotemporal Sclerosismentioning
confidence: 99%